On the use of agricultural system models for exploring technological innovations across scales in Africa: A critical review - Reimund P. Rötter; Fanou L. Sehomi; Jukka G. Höhn; Jarkko K. Niemi; Marrit Van den Berg (University of Bonn, Center for Development Research (ZEF), 2016)
The major challenge of the 21st century is to achieve food security under, roughly, a doubling in food demand by 2050 compared to present, and producing the additional food under marked shifts in climatic risks and with environmentally sound farming practices. Sustainable intensification of agricultural production is required that meets the dual goal of improved environmental sustainability and economic efficiency. Ex ante evaluation of technological innovations to support agricultural production and food security taking into account the various future risks can substantially contribute to achieve this. Here we perceive technological innovations as new or improved agro-technologies and -management practices, such as new breeds, integrated soil fertility practices or labour-saving technologies meeting the goals of sustainable intensification. In this report we present results from three systematic reviews: one on the use of biophysical modelling, the second and third on the use of bio-economic modelling at farm scale and agro-economic modelling at higher aggregation levels, for ex ante evaluation of the effects of (agro-) Technological Innovations (ag-TIs) on sustainable agriculture and food security indicators. To this end, we searched the SCOPUS database for journal articles published between 1996 and 2015. We considered modelling studies at different spatial scales with particular attention to local to national scale studies for the twelve PARI focal countries in Africa1. But we also included studies for all other African countries as well as a few studies at supra-national/continental scale. Both, "quick wins" as well as long term benefits from ag-TIs were of interest. The various ag-TIs were furthermore grouped into four classes: (1) water/soil moisture (2) soil nutrients/conservation (3) crop/cropping system, (4) other ag-TIs or (5) combinations of 1 to 4. For each paper, we tried to identify the primary ag-TI analysed, and if there was equal emphasis to more than one, we classified them as combinations. It should be borne in mind that there is some subjectivity in classifying the papers in this way ...
Keywords: C61; C63; C65; C68; D81; O32; 330; Africa; agricultural system models; agro-economic modelling; biophysical modelling; ex ante evaluation; risk; technological innovation; yield variability